Integration of process and quality control using multi-agent technology - Cristalli, Cristina (2014)
The paper introduces a new approach on design of distributed manufacturing control systems. It will be shown how multi-agent principles, self-learning, self-adaptation and a new engineering method for distributed production systems can be used to enhance integration of production control process quality control. It will be highlighted how multi-agent systems may be implemented to enforce interaction of manufacturing execution system and distributed control system, enhancing the exploitation of all available information at the quality control and process control levels. Additional focus is set on production process modeling, quality control algorithms and an engineering methodology integrating all these aspects within. The final results are validated in the field of white ware using a washing machine production line.